Identification of C2–C5 products from CO2 hydrogenation over PdZn/TiO2–ZSM-5 hybrid catalysts. (19th April 2021) - Ruiz Esquius, Jonathan; Bahruji, Hasliza; Bowker, Michael; Hutchings, Graham J.
Abstract : PdZn/TiO2 combined with ZSM-5 zeolites allowed for consecutive CO2 hydrogenation to CH3 OH, CH3 OH dehydration to DME, and MTH/DMTH in a one-pass single bed reactor. PdZn alloys, although stable at high temperature, hydrogenate olefins, limiting MTH/DMTH chain growth. Abstract : The combination of a methanol synthesis catalyst and a solid acid catalyst opens the possibility to obtain olefins or paraffins directly from CO2 and H2 in one step. In this work several PdZn/TiO2 –ZSM-5 hybrid catalysts were employed under CO2 hydrogenation conditions (240–360 °C, 20 bar, CO2 /N2 /H2 = 1 : 1 : 3) for the synthesis of CH3 OH, consecutive dehydration to dimethyl ether and further oxygenate conversion to hydrocarbons. No significant changes after 36 h reaction on the methanol synthesis catalyst (PdZn/TiO2 ) were observed by XRD, XAS or XPS. No olefins were observed, indicating that light olefins undergo further hydrogenation under the reaction conditions, yielding the corresponding alkanes. Increasing the aluminium sites in the zeolites (Si : Al ratio 80 : 1, 50 : 1 and 23 : 1) led to a higher concentration of mild Brønsted acid sites, promoting hydrocarbon chain growth.